Stability and Reactivity of Cyclometallated Naphthylamine Complexes in Pd–C Bond Insertion Reactions with Coordinated Alkynylphosphanes - Chen, Shuli (2014)
Phenylbis(phenylethynyl)phosphane PhP(C≡CPh)2 coordinates regiospecifically to the α-methyl-chiral ortho-platinated and -palladated naphthylamine units at the positions trans to the nitrogen donors. The P→Pt coordination bond is kinetically inert, whereas the P→Pd bond is labile. Upon heating of these phosphane complexes at 70 °C, one of the C≡C bonds in the coordinated PhP(C≡CPh)2 was activated towards an intermolecular Pd–C bond insertion reaction with an external ortho-palladated naphthylamine ring. No intramolecular insertion reaction occurred. In contrast to its palladium analogue, the ortho-platinated ring is not reactive towards coordinated PhP(C≡CPh)2, although it can promote the Pd–C bond insertion reaction. However, despite the high kinetic stability of the P→Pt coordination, the organoplatinum unit is a noticeably weaker activator than its organopalladium counterpart. The chirality of the reacting ortho-metallated naphthylamine ligand exhibited high stereochemical influence on the formation of the new stereogenic phosphorus center during the course of these C–C bond-formation reactions. The coordination chemistry and the absolute stereochemistry of the dimetallic products were determined by single-crystal X-ray crystallographic analysis.